Sociolinguistics of Names of Hotels in Accra: A Linguistic Landscape Perspective - Ebenezer Agbaglo; Joseph Benjamin Archibald Afful (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
In recent times, the language in public spaces (as seen in street names, school names, names of buildings, names of metro stations, names of tourist attractions, and commercial signs) has attracted scholarly attention in onomastics, with the focus on how it reflects the linguistic situation of urban landscapes and how it can be used to construct several identities. The present study aimed to investigate names of hotels in Accra – the capital city of Ghana, with considerable financial, cultural, and industrial significance – using Landry & Bouris’s (1997) Linguistic Landscape as a theory. The data comprises 160 hotel names accessed from the website of Yello Ghana, a well-known business directory. The analysis revealed, first, that most of the hotels deployed English monolingual names, with a few utilising bilingual names. Closely allied to this finding is the trend towards globalisation, as captured in some names of hotels. These key findings have implications for the scholarship in onomastics, urban landscape, language policy and planning, and further research.